Plasmachemical Plant for NPP Drain Water Treatment - Zabulonov, Yu.L.; Burtnyak, V.M.; Odukalets, L.A.; Alekseeva, O.V.; Petrov, S.V. (Science and Innovation, 2024)
Introduction. As a result of the operation of nuclear power plants, liquid radioactive waste (LRW) is formed, which consist mainly of drain water. Technologies and technical means of drain water treatment have a number of disadvantages that make the treatment long and expensive. Problem Statement. One of the most promising advanced methods of LRW treatment is the plasma chemical method that has not been used in domestic practice. An experimental study of plasma chemical method for the treatment of radioactive waste from nuclear power plants has been performed for ensuring safe and efficient treatment of liquid radioactive waste in order to make it suitable for temporary storage. Purpose. Development of modern domestic equipment for concentrating and removing the radioactive elements from solutions of complex salt composition. Materials and Methods. When creating a plasma chemical plant, methods for mathematical and computer modeling, full-scale prototyping, and machine design have been used. Special solutions containing Cs+, Sr2+, Co2+, Cu2+, and Mn2+ ions, as well as solutions with organic components, have been prepared to study the technical characteristics of the developed plasma chemical plant and its features. Results. An experimental electric discharge plant for using the plasma chemical technologies for the treatment of liquid radioactive waste, in particular, drain water, has been created and studied; its characteristics have been determined. Conclusion. The developed prototype plant enables to carry out integrated treatment of LRW and to significantly reduce its volume. Due to one-stage process, the plasma-chemical method is effective in solving the problems of LRW utilization.